2019
DOI: 10.1111/vsu.13305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between optical coherence tomographic and histopathologic appearances of artifacts caused by common surgical conditions and instrumentation

Abstract: Objective To document the appearance of artifacts created by commonly encountered surgical conditions and instrumentation on optical coherence tomography (OCT) and to compare these findings with histopathology. Study design Ex vivo study. Animals Five canine cadavers. Methods Skin, subcutaneous fat, skeletal muscle, and fascia samples were obtained from fresh canine cadavers. Blood pooling, hemostatic crushing, scalpel blade cut, monopolar electrosurgery, bipolar vessel sealing device, and ultrasonic energy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…These images show tissue microstructure comparable to that seen on a low‐magnification histology slide 12‐16 . The images can be interpreted with a high diagnostic accuracy by observers in various specialties after a short standardized training module, and can accurately differentiate normal tissues from canine soft tissue sarcoma and human breast cancer 10‐15,17,18 . In light of these findings, the authors suspect that OCT could have applications in guiding pathology sampling in excised tumour specimens to aid in surgical margin assessment.…”
Section: Introductionmentioning
confidence: 72%
“…These images show tissue microstructure comparable to that seen on a low‐magnification histology slide 12‐16 . The images can be interpreted with a high diagnostic accuracy by observers in various specialties after a short standardized training module, and can accurately differentiate normal tissues from canine soft tissue sarcoma and human breast cancer 10‐15,17,18 . In light of these findings, the authors suspect that OCT could have applications in guiding pathology sampling in excised tumour specimens to aid in surgical margin assessment.…”
Section: Introductionmentioning
confidence: 72%
“…This higher scattering appearance has been characterized in a recent study in canine cadavers. 32 Instrument artefacts and blood pooling were included in the training presentation for observers but may have led to some diagnostic uncertainty. There is the potential this may be improved with increased training and experience of observers.…”
Section: Determining the Diagnostic Accuracy Of Oct Imaging For Completeness Of Surgical Excision Of Cmt (Ex Vivo And In Vivo)mentioning
confidence: 99%
“…The light waves generated by the OCT probe are reflected off the microscopic tissue structures and images are created based on cellular density and organization 1‐4 . Only a few previous studies have ever reported the use of this technology in dogs 5‐7 . These studies were able to describe the visual characteristics of normal tissues, common surgical artifacts seen on OCT imaging, the appearance of soft tissue sarcoma (STS) compared with normal tissues, and even develop a textural analysis algorithm to differentiate the dense, highly‐scattering STS from similarly highly‐scattering normal musculature 5‐7 …”
Section: Figurementioning
confidence: 99%